A new vinyl selenone-based domino approach to spirocyclopropyl oxindoles endowed with anti-HIV RT activity. Issue 6 (12th January 2016) - Palomba, M.; Rossi, L.; Sancineto, L.; Tramontano, E.; Corona, A.; Bagnoli, L.; Santi, C.; Pannecouque, C.; Tabarrini, O.; Marini, F.
Abstract : A flexible synthesis of spirocyclopropyl oxindoles from vinyl selenones and oxindoles via a domino Michael addition/proton transfer/cyclization sequence has been developed. Abstract : Herein, we disclose a general and flexible access to spirocyclopropyl oxindoles by a domino Michael/intramolecular nucleophilic substitution pathway with variously substituted vinyl selenones and enolizable oxindoles in aqueous sodium hydroxide solution. The spirocyclopropyl oxindole being a privileged scaffold, some of the synthesized compounds were selected for biological evaluation. Compound3m showed selective anti-HIV-1 activity thanks to its ability to inhibit the reverse transcriptase.